Correction: Patterned liquid metal contacts for high density, stick-and-peel 2D material device arrays. Issue 7 (10th February 2020) - Chen, Yen-Lin; Nguyen, Yen; Wu, Shuo-En; Chin, Yi-Chun; Chuang, Chiashain; Hsieh, Ya-Ping; Hofmann, Mario
Abstract : Correction for 'Patterned liquid metal contacts for high density, stick-and-peel 2D material device arrays' by Yen-Lin Chen et al., Nanoscale, 2018, 10, 14510–14515.